2023
DOI: 10.1002/ps.7451
|View full text |Cite
|
Sign up to set email alerts
|

Exploring boron applications in modern agriculture: Antifungal activities and mechanisms of phenylboronic acid derivatives

Abstract: Background The unreasonable use of chemical fungicides causes common adverse consequences that not only affect the environment, but also cause resistance and resurgence problems of plant pathogens, which are extremely harmful to human health, the economy, and the environment. Based on the rich biological activities of boron‐based compounds, 82 phenylboronic acid derivatives were selected and their antifungal activities against six agricultural plant pathogens were determined. Combined with transcriptomics tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Despite the vast body of scientific evidence, it has not been conclusively reported that B is necessary for both humans and animals. In fact, several BCCs, such as borates, boronates, and boronic acids, exhibited interesting biological activities, including antiviral [2], antibacterial [3,4], antifungal and antiparasitic [5,6], antioxidant [7,8], wound healing [9], anti-inflammatory [10,11], antimutagenic [12], anticancerogenic [13,14], radiobiological [15], and neuroprotective properties [16,17]. Interestingly it was found that people living in B-rich regions had less cancer incidence than the people living in B-poor regions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the vast body of scientific evidence, it has not been conclusively reported that B is necessary for both humans and animals. In fact, several BCCs, such as borates, boronates, and boronic acids, exhibited interesting biological activities, including antiviral [2], antibacterial [3,4], antifungal and antiparasitic [5,6], antioxidant [7,8], wound healing [9], anti-inflammatory [10,11], antimutagenic [12], anticancerogenic [13,14], radiobiological [15], and neuroprotective properties [16,17]. Interestingly it was found that people living in B-rich regions had less cancer incidence than the people living in B-poor regions [18].…”
Section: Introductionmentioning
confidence: 99%